Інформаційна взаємодія Національної поліції України з органами публічної влади та громадськістю - Процких, О. Ю.; Protskykh, O. Y. (Право і безпека. - 2015. - № 4 (59). - С. 50-55., 2015)
Викладено напрямок удосконалення діяльності Національної поліції України, що обумовлює створення методів і форм правового регулювання та забезпечення ефективності її діяльності з питань інформаційної взаємодії з органами публічної влади.

The direction of improving the National Police of Ukraine, which stipulates the establishment of methods and forms of legal regulation and ensuring its effectiveness on information cooperation matters with the public authorities is provided. It is pointed on the necessity of regulatory streamlining of terminology understanding of information interaction as a special type of cooperation while performing specific tasks, including in the sphere ofinformation and search, information and analytical work. It is found out that the information police interaction – is a timely, systematic transmission of objective information within law enforcement matters from one subject of interaction to another one. The system of mutual information is based on the selection of information to meet the needs of the parties that interact. An important stage of information interaction is the proper response to the transferred information. The author has offered to combine existing forms of information interaction in conditional blocks and develop a systematic methodology for the organization of information interaction of police units with other law enforcement agencies, state agencies, local self-governments and the public.

Изложено направление усовершенствования деятельности Национальной полиции Украины, что обуславливает создание методов и форм правового регулирования и обеспечения эффективности её деятельности по вопросам информационного взаимодействия с органами публичной власти.
Процких, О. Ю. Інформаційна взаємодія Національної поліції України з органами публічної влади та громадськістю / О. Ю. Процких // Право і безпека. - 2015. - № 4 (59). - С. 50-55.
Protskykh, O.Y. (201 5), “Information interaction of the National Police of Ukraine with public authorities and the public” [“Informatsiina vzaiemodiia Natsionalnoi politsii Ukrainy z orhanamy publichnoi vlady ta hromadskistiu”], Pravo i Bezpeka, No. 4, pp. 50–55.
Keywords: Адміністративне право та процес. Адміністративна діяльність. Administrative Law and Procedure. Administrative Activity. Административное право и процесс. Административная деятельность; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; National police of Ukraine; Национальная полиция Украины; Національна поліція України. National police of Ukraine. Национальная полиция Украины; інформаційна взаємодія; партнерство; правове регулювання; органи публічної влади; громадськість; information interaction; partnership; legal regulation; public authorities; public; информационное взаимодействие; партнерство; правовое регулирование; органы публичной власти; общественность